Sequences of the Plasmodium falciparum cytoadherence-linked asexual protein 9 implicated in malaria parasite invasion to erythrocytes (2010)
In this study, we synthesized the complete sequence of the CLAG-9 protein as 67 20-mer-long non-overlapped peptides and assessed their ability to bind to erythrocytes in receptor-ligand assays. Twenty CLAG-9 peptides were found to have specific high-affinity binding ability to erythrocytes (thereby named as HABPs), with nanomolar dissociation constants. CLAG-9 HABPs interacted with different erythrocyte surface receptors having apparent molecular weights of 85, 63 and 34 kDa. CLAG-9 HABPs binding was also affected by pre-treatment of RBCs with enzymes and inhibited erythrocyte invasion in vitro by up to 72% at 200 ?M. These results suggest that some protein fragments of CLAG-9 may be part of the molecular machinery used by malaria parasites to invade erythrocytes, hence supporting their study as possible vaccine candidates. © 2010 Elsevier Ltd. All rights reserved.